Thymic Egress Is Regulated by T Cell-Derived LTβR Signal and via Distinct Thymic Portal Endothelial Cells - Xia, Huan; Zhong, Suijuan; Zhao, Yixiao; Ren, Boyang; Wang, Zhongnan; Shi, Yaoyao; Chai, Qian; Wang, Xiaoqun; Zhu, Mingzhao (Frontiers in Immunology, 2021)
Thymic blood vessels at the perivascular space (PVS) are the critical site for both homing of hematopoietic progenitor cells (HPCs) and egress of mature thymocytes. It has been intriguing how different opposite migrations can happen in the same place. A subset of specialized thymic portal endothelial cells (TPECs) associated with PVS has been identified to function as the entry site for HPCs. However, the cellular basis and mechanism underlying egress of mature thymocytes has not been well-defined. In this study, using various conventional and conditional gene deficient mouse models, we first confirmed the role of endothelial lymphotoxin beta receptor (LTbR) for thymic egress and ruled out the role of LTbR from epithelial cells or dendritic cells. In addition, we found that T cell-derived ligands lymphotoxin (LT) and LIGHT are required for thymic egress, suggesting a crosstalk between T cell and endothelial cells or thymic egress control. Furthermore, immunofluorescence staining analysis interestingly showed that TPECs are also the exit site for mature thymocytes. Single-cell transcriptomic analysis of thymic endothelial cells (ECs) suggested that TPECs are heterogeneous and can be further divided into two subsets depending on BST-1 expression level. Importantly, BST-1hi population is associated with thymic egressing thymocytes while BST-1lo/- population is associated with HPC settling. Thus, we have defined a LT/LIGHT-LTbR signaling mediated cellular crosstalk regulating thymic egress and uncovered distinct subsets of TPECs controlling thymic homing and egress, respectively.